(untitled) (Mugda Medical College Journal, 2025)
Ageing associated with multiple comorbidities tends to expose elderly population to the risk of potentially inappropriate medications (PIMs), which may turn into an important contributing factor for negative health impacts, e.g., adverse drug reactions, hospitalization, increased morbidity and mortality. A cross-sectional, observational study was conducted to assess the prevalence of potentially inappropriate medications (PIMs) as prescribed to geriatric patients in an out-patient department (OPD) of Dhaka Medical College Hospital, which is a tertiary level teaching hospital in Dhaka, Bangladesh. The study was carried out between January and December of 2021. A total of 114 elderly patients (e” 60 years) were enrolled in this study. Data was collected by face-to-face interview and from patients’ prescriptions using a pre-tested semi-structured data collection sheet. Data were reviewed according to American Geriatrics Society endorsed 2019 Updated AGS Beers Criteria and analyzed using SPSS version 22.0. Most of the respondents belonged to 60-69 years age group (69.3%) and the mean age was 68.25±7.2 years. 59.6% of the patients were male and 40.4% were female. A total of 31(27.19%) elderly patients were found having potentially inappropriate medications (PIMs), as prescribed from the outdoor service. The highest number of PIMs was found in the e”80 years age group (44.44%), followed by 60-69 years (26.58%) and 70-79 years (23.08%) age groups (p=0.057). 28.3% of female patients got PIMs, while 26.5% of males were prescribed PIMs (p=0.833). In our study, the most common PIMs identified was pain medication (NSAIDs) (51.62%), followed by benzodiazepines (22.58%), antidepressants (12.9%), proton-pump inhibitors (6.45%), and first-generation antihistamines (6.45%). Mugda Med Coll J. 2024; 7(2): 72-76